Antara Hukum dan Kepentingan Korporasi: Tinjauan Etika Profesi pada Kasus Kenny Sonda - Nagita Dyah Puspitasari; Irma Cahyaningtyas (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2025)
The case of Kenny Sonda, an in house counsel who was criminalized for his legal opinion, highlights the ethical dilemma between professional independence and loyalty to the company. This raises concerns about the protection of the legal profession, especially for in house counsels. This research aims to analyze this conflict through the perspectives of deontological theory, which focuses on moral obligations, and teleological theory, which considers the consequences of decisions. Using a normative legal analysis method, this study evaluates the relevance of both theories in formulating legal opinions ethically and strategically. The results show that applying a combination of both theories can help in house counsels navigate ethical dilemmas without compromising professionalism or violating ethical codes. The conclusion emphasizes the need for stronger legal protection for the legal profession and the importance of companies creating policies that support the independence of internal legal advisors.